Stimulation of Suicidal Erythrocyte Death by Naphthazarin. Issue 6 (16th June 2015) - Aljanadi, Omar; Alzoubi, Kousi; Bissinger, Rosi; Lang, Florian
Abstract: The 1, 4‐naphthoquinone derivative naphthazarin may trigger apoptosis and is thus considered for the treatment of malignancy. On the other hand, naphthazarin decreases neurotoxicity. In analogy to apoptosis of nucleated cells, erythrocytes may enter eryptosis, the suicidal erythrocyte death characterized by cell shrinkage and by cell membrane scrambling with translocation of phosphatidylserine to the erythrocyte surface. Signalling leading to triggering of eryptosis include increase in cytosolic Ca 2+ ‐activity ([Ca 2+ ]i ), ceramide and oxidative stress. The present study explored whether naphthazarin impacts on eryptosis and, if so, to unravel underlying mechanisms. To this end, erythrocyte volume was estimated from forward scatter, phosphatidylserine abundance at the erythrocyte surface from FITC‐annexin‐V‐binding, [Ca 2+ ]i from Fluo3 fluorescence, reactive oxidant species (ROS) from 2′, 7′‐dichlorodihydrofluorescein diacetate (DCFDA) fluorescence and ceramide abundance at the erythrocyte surface from binding of fluorescent antibodies in flow cytometry. As a result, a 24‐hr exposure of human erythrocytes to naphthazarin (10 μm ) significantly decreased erythrocyte forward scatter, significantly increased the percentage of annexin‐V‐binding cells, significantly increased ceramide abundance at the erythrocyte surface and significantly increased ROS. The effect of naphthazarin on annexin‐V‐binding was not significantly blunted by removal of extracellular Ca 2+ . In conclusion, naphthazarin stimulates eryptosis, an effect at least in part due to oxidative stress and enhanced ceramide abundance at the erythrocyte surface.